Application of Clinical Pharmacology Principles in Drug Development of Modified‐Release Products: Leveraging Exposure‐Response Information to Support Approval. (26th May 2020) - AbuAsal, Bilal S.; Hamed, Salaheldin S.; Ahmed, Mariam A.; Al‐Mansour, Lana; Uppoor, Ramana; Mehta, Mehul
Abstract: The development of modified‐release (MR) drug products aims to address a clinical need such as improving patient compliance. There are multiple pathways and development strategies for the registration and approval of MR products. The development strategy of an MR product is usually dependent on the availability and pharmacokinetic/pharmacodynamics (PK/PD) characteristics of the reference drug product, that is, an immediate‐release (IR) product or a reference MR. Compared with a reference IR product, an MR product is likely to have a different PK profile over the least common dosing time due to unequal dosing intervals. In case of differences in PK profiles between the MR product and the reference product, confirmatory efficacy and safety studies may be needed to support registration. In some cases, however, a thorough clinical PK/PD characterization may provide sufficient basis to support the approval of the proposed MR product without the need for additional safety and efficacy studies. This article summarizes the US Food and Drug Administration experience and the regulatory considerations supporting the approval of MR products in the past 6 years and discusses cases in which clinical pharmacology and PK/PD information were leveraged to support approval without the need for additional clinical studies. Details of all these cases are available in the public domain. In 2 cases a well‐characterized exposure‐response relationship provided sufficient justification that differences in the shape of the PK profiles were not clinically relevant. In the remaining 3 cases a thorough characterization of the PK profile along with a risk‐based approach provided bases for approval.